Potential Risk Management Improvements for Institutional Investors Enlightened by Behavoural Finance - Wang, Yilin (2012)
The dissertation is focused on the implications of behavioural finance for risk management practices of institutional investors. My contribution consists of exploring potential improvements in risk management for institutional investors based on the seminal results of behavioural finance, and the findings from the mini case studies on the risk management practices of 10 UK institutional funds that ranked top 50 in December 2011 by Investment Management Association (IMA).